2015
DOI: 10.1016/j.celrep.2015.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stranded DNA-Binding Transcriptional Regulator FUBP1 Is Essential for Fetal and Adult Hematopoietic Stem Cell Self-Renewal

Abstract: The ability of hematopoietic stem cells (HSCs) to self-renew is a prerequisite for the establishment of definitive hematopoiesis and life-long blood regeneration. Here, we report the single-stranded DNA-binding transcriptional regulator far upstream element (FUSE)-binding protein 1 (FUBP1) as an essential factor of HSC self-renewal. Functional inactivation of FUBP1 in two different mouse models resulted in embryonic lethal anemia at around E15.5 caused by severely diminished HSCs. Fetal and adult HSCs lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 33 publications
(38 reference statements)
1
48
0
Order By: Relevance
“…Contrary to the results here, the investigators report that HSCs of FBP-deficient mice proliferate poorly but differentiate properly. 47 Note that this study relied on gene-trap and shRNA targeting of the Fubp1 allele or its mRNA; neither of these methods assures the complete absence of functional FBP as guaranteed by the germline deletion of the FBP's nucleic acid binding domain in the current experiments. Hypomorphic but not null FBP activity in these systems is strongly suggested by comparison of the competitive transplantation assays.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the results here, the investigators report that HSCs of FBP-deficient mice proliferate poorly but differentiate properly. 47 Note that this study relied on gene-trap and shRNA targeting of the Fubp1 allele or its mRNA; neither of these methods assures the complete absence of functional FBP as guaranteed by the germline deletion of the FBP's nucleic acid binding domain in the current experiments. Hypomorphic but not null FBP activity in these systems is strongly suggested by comparison of the competitive transplantation assays.…”
Section: Discussionmentioning
confidence: 99%
“…FUBP1 knockdown in human hepatocellular carcinoma (HCC) cell lines also decreases proliferation, and impairs tumour formation in mouse xenograft models [127]. Essential functions in HSC self-renewal were revealed using Fubp1 gene trap mice, with embryonic lethality (around E15.5) associated with anaemia [128]. Secondary transplantation assays for long-term repopulating hematopoietic stem cells (LT-HSCs) revealed reduced blood cell reconstitution for Fubp1 knockdown.…”
Section: Developmental Function Of Fubp1mentioning
confidence: 99%
“…Secondary transplantation assays for long-term repopulating hematopoietic stem cells (LT-HSCs) revealed reduced blood cell reconstitution for Fubp1 knockdown. Fubp1 -deficient adult HSCs exhibited increased expression of key cell cycle (cyclin-dependent kinase inhibitor, p21 ) and pro-apoptotic ( Noxa ) genes based on mRNA expression profile data [128]. Given that the haematopoietic lineage displays specific sensitivity to MYC levels [32], and the ability of MYC to repress p21 expression [129], the Fubp1 knockout phenotype suggests that MYC could be a key downstream target that mediates these effects.…”
Section: Developmental Function Of Fubp1mentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies demonstrated that reduced FUBP1 is required for MYC expression and proliferation in ex vivo cultured cells. 35,36 Recent FUBP1 gene trap 37 and knockout studies 38 revealed essential functions in haematopoietic stem cell (HSC) self-renewal, which is associated with anaemia and embryonic lethality. Interestingly, MYC mRNA levels vary drastically between individual ex vivo cultures of FUBP1 knockout mouse embryo fibroblasts (MEFs) harvested from different FUBP1 embryos.…”
Section: Developmental Function Of Fubp1mentioning
confidence: 99%